Analisis Faktor – Faktor Konsumsi Beras Organik Dan Non Organik Di Padang Panjang Sumatera Barat - Yimmi Syavardie; Imran Imran; Juarsa Badri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Food is an important and strategic commodity, because it is an essential human need that must be fulfilled at all times. Food needs need to be made available in sufficient quantities, adequate quality, safe for consumption and easily obtainable at prices affordable by all levels of society. The study was conducted on organik rice distributors located in Padangpanjang, West Sumatra. Based on the variables tested in this study and including dummy, the most dominant factor of consumption of organik rice is the variable that has a loading value above 0.5, this factor is the income factor ( income and expenditure), personal factors (level of education and delivery), and external factors (availability, vehicle ownership and external motivation). From the analysis and observations made, it can be concluded that consumers in consuming organik rice are still few and not from their own desires. Consumers in consuming organik rice only follow along with other consumers or call on consumers who have consumed organik rice so that continuous public awareness must be given to the benefits of organik rice.